Global Volatility and Forex Returns in East Asia - Kalra, Sanjay (Washington, D.C. : International Monetary Fund, 2008)
During 2001-07, increases in mature market volatility were associated with declines in forex returns for East Asian countries, consistent with an overall "flight to safety" effect. Estimates from GARCH models suggest that a 5 percentage point increase in mature market equity volatility generated an exchange rate depreciation of up to 1\2 percent. This sensitivity rose during the latter period in the sample, suggesting greater integration of Asian financial markets with global markets. Unconditional standard deviations estimated from these models also provide operational measures of "long-term" and "excess" volatility in forex markets. Long-run forex volatility declined as Asian economies settled down with generally stronger fundamentals in the post-crisis period to more flexible regimes along with a generally lower level of mature market volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet